Designing the social life of books and e-books - Hupfeld, Annika (2017)
E-books have seen a significant proliferation over recent years. In the UK, about a third of the population today owns an e-reader with about half either owning an e-reader or tablet. Nevertheless, only about 4% of readers have moved to reading e-books only. These numbers suggest that, while e-books have caught on among a large number of users, they seem to complement rather than replace books. In light of the significance of books to past and contemporary cultures and societies it is little surprising that the emergence of e-reading technologies has sparked a plethora of writing on the topic, particularly in journalism and the humanities. With a common focus on the relative merits of books and e-books, and ultimately, their respective futures (some writers go as far as either mourning or celebrating the death of the book), the debate largely suffers from a technological determinist stance, neglecting the role of social practice as a driving force in technology adoption and use. Regardless, the sheer volume of the discourse suggests that something important is at stake in the move from analogue to digital reading technologies and that books continue to be valued as physical artefacts in the digital age, if not with more fervour than ever. What is surprising then is the lack of empirical research aiming to understand how books and e-books are used and valued in everyday life. Existing work in the area is almost exclusively concerned with practices of reading, with a particular emphasis on reading in academic and professional environments, thereby not only disregarding the social and material nature of reading, but also the rich life of the book beyond its role as a reading technology. The aim of this thesis then is to provide an understanding of the practices and values surrounding books and e-books in everyday life. Based on this understanding, it further aims to explore alternatives to the current e-reading ecosystem through designs that are sensitive to the some of the broader values people associate with books and e-books. To do so, it takes a situated approach to studying books and e-books as they are used over the course of their lifecycle inside and outside the home. Through a combination of a series of in-depth interviews, guided ‘home tours’, and participant diaries ‘context-rich’ data on people’s uses of and orientations towards books and e-books are gathered. Subsequently, design responses are iteratively developed before being returned to readers for analysis. The contribution of this thesis is fourfold: (1) an account of the socially and materially situated practices associated with books and e-books inside and outside the home, (2) an explication of the distinct, yet complementary, values reflected in and driving book and e-books use, (3) an explication of the ways in which developing a sense of self and connecting with others are actualized through the use of books and e-books, and (3) the development and in situ analysis of a design exemplar in support of these goals.